Gold nanoparticle conjugated magnetic beads for extraction and nucleation based signal amplification in lateral flow assaying - Sharma, Antareep (2022)
Analogues and interferents present in complex matrices like blood, plasma or serum influence lateral flow assay (LFA) responses, resulting in weak signals which compromise the limit of detection. Herein, we report a gold nanoparticle conjugated magnetic bead (GMB) based LFA approach for extraction and sensitive visual assaying of proteins in plasma. To validate the approach GMB, conjugated with anti-Troponin I antibodies, is used to capture cardiac marker Troponin I-C-T (cTnICT) in plasma that subsequently flows through on LFA membrane via a test zone containing anti-Troponin C antibodies. The capture of cTnICT-GMB complexes at the test zone produces a characteristic brownish band, enabling concentration dependent visual detection of cTnICT. Subsequently, contrast of these bands are enhanced by a nucleation approach, that utilizes the gold nanoparticles on GMB in the test bands as seed materials for growth of more visible gold clusters, improving visual detection limit of the assay to 0.1 ng/mL in plasma within 20 min, using low sample volumes (<100 μL). The proposed approach exploits the dual functionality of GMBs for efficient preconcentration and facile signal amplification. This assay offers a promising avenue for sensitive detection of analytes in complex matrices at clinically relevant concentrations without requiring tedious sample pre-treatment protocols.